2013
DOI: 10.4049/jimmunol.1202495
|View full text |Cite
|
Sign up to set email alerts
|

IL-23–Independent Induction of IL-17 from γδT Cells and Innate Lymphoid Cells Promotes Experimental Intraocular Neovascularization

Abstract: Choroidal neovascularization (CNV) is a characteristic of age-related macular degeneration. Genome-wide association studies have provided evidence that the immune system is involved in the pathogenesis of age-related macular degeneration; however, the role of inflammatory cytokines in CNV has not been established. In this study, we demonstrated that IL-17 had a strong potential for promoting neovascularization in a vascular endothelial growth factor–independent manner in laser-induced experimental CNV in mice.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
78
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(82 citation statements)
references
References 41 publications
3
78
0
1
Order By: Relevance
“…have demonstrated that IL-17 has a strong potential for stimulating neovascularization in a VEGF-independent manner in laser-induced experimental CNV model23. Furthermore, the suppressive effect of anti-IL-17 therapy on CNV volume and area was similar to that of anti-VEGF therapy, and the combination of anti-VEGF and anti-IL-17 therapy was more effective23. The observed presence of elevated intraocular IL-17 in our study indicates that IL-17 may be involved in the pathogenesis of ICNV.…”
Section: Discussionmentioning
confidence: 99%
“…have demonstrated that IL-17 has a strong potential for stimulating neovascularization in a VEGF-independent manner in laser-induced experimental CNV model23. Furthermore, the suppressive effect of anti-IL-17 therapy on CNV volume and area was similar to that of anti-VEGF therapy, and the combination of anti-VEGF and anti-IL-17 therapy was more effective23. The observed presence of elevated intraocular IL-17 in our study indicates that IL-17 may be involved in the pathogenesis of ICNV.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it was demonstrated that IL-17 alone had no impact on vessel growth, although it can potentiate the effect of other angiogenic factors such as VEGF, basic fibroblast growth factor (bFGF) and hepatocyte growth factor (HGF) [72]. Recent findings have shown that combined production of IL-17 from γδT cells and innate lymphoid cells was responsible for the increased neovascularization observed in experimental model of CNV [74]. As such, the precise role of IL-17 in regulating angiogenesis in the eye remains unclear.…”
Section: The Role Of Adaptive Immunity In Ocular Angiogenesismentioning
confidence: 99%
“…Recent reports have demonstrated involvement of the inflammatory cytokine interleukin-17 (IL-17; R&D Systems, Minneapolis, MN, USA) in the pathogenic inflammation of AMD. [8][9][10] Interleukin-17 is the signature cytokine of T-helper 17 (Th17) cells and plays a pivotal role in inducing expression of proinflammatory cytokines and chemokines in the pathogenesis of autoimmune and inflammatory diseases. 11 In addition to its powerful proinflammatory effect, IL-17 has the potential to upregulate VEGF from rheumatoid arthritis (RA) synoviocytes and to promote development of microvessel structures in RA and tumor growth.…”
mentioning
confidence: 99%